Determination of wind potential characteristics and techno-economic feasibility analysis of wind turbines for Northwest Africa. (1st March 2021) - Bilal, Boudy; Adjallah, Kondo Hloindo; Yetilmezsoy, Kaan; Bahramian, Majid; Kıyan, Emel
Abstract: This study introduced an investigation to evaluate spatial and temporal variations of the wind potential for the techno-economic feasibility analysis of the energy production in Northwest Africa (a case of Mauritania). The present research was introduced as the first attempt to appraise the spatio-temporal influence of the wind energy production in Mauritania, and particularly focused on analyzing seasonal, daily, and turbulence index on the available wind potential in this region. Data measured every 10 min over one-year period were collected from eight sites (with three different height levels) located mainly on the west coast of Mauritania, and the annual average of the wind characteristics were determined. Power density, Weibull parameters, turbulence indices, and power-law exponents were estimated based on seasonal and daily wind analyses. Comparative studies of the power density potential of the wind on different sites were also conducted while investigating the influence of seasons, height of the wind turbines, wind directional distributions, and daily characteristics. Investigations regarding the generated energy from the wind turbine and the related capacity factor were performed based on eight particular wind turbines (Ecotècnia-44, Ecotècnia-48, Nordex-N50, Neg-Micon, Vestas-V66, Power-Wind-90, Bonus-2MW, and Vestas-V90). Results showed that the power-law exponent was higher where the turbulence index was low. The analysis of the power distribution allowed concluding on the energy availability according to the influent variables. Findings of the present techno-economic analysis (for electricity generation from the planned wind energy systems) revealed that the best cost of energy (ranging from 0.0187 €/kWh to 0.0596 €/kWh) was observed for the wind turbine Ecotècnia-48 on all sites. Graphical abstract: Image 1 Highlights: Spatio-temporal variations of the wind potential were explored in Mauritania for the first time. Wind potential for electricity generation was characterized for eight sites with three height levels. Wind direction was more stable in the rainy season than in dry season on all sites. Annual mean turbulence index and power law exponent showed an opposite relationship. Techno-economic feasibility analysis revealed that the best cost of energy was 0.0187 €/kWh.